NUP155 and NDC1 interaction in NSCLC: a promising target for tumor progression - Li, Kai-Min; Meng, Li-Fei; Yang, Zhi-Hao; Hu, Wen-Tao (Frontiers in Pharmacology, 2024)
BackgroundNUP155 was reported to involve breast invasive carcinoma and hepatocellular carcinoma. We hypothesized that NUP155 and NDC1impacted the progression of NSCLC.MethodsThe dataset was analyzed to find differentially expressed genes. Functional enrichment analysis and Kaplan-Meier survival analysis were performed for differentially expressed genes. Western blot, Clone formation assay, Transwell assay and CCK-8 assay were performed to determine the performance and role of the target gene in NSCLC.ResultsThe research found that the NUP family played a role in various diseases. Differential expression analysis and survival analysis were performed to identify 6 related-genes, including NUP155, NDC1, KPNA2, MAD2L1, NUP62CL, and POM121L2NUP155 and NDC1 could interact with NUP53, respectively. This effect was necessary to complete the assembly of the nuclear pore complex.ConclusionNUP155 interacted with NDC1 to complete the assembly of the nuclear pore complex, which promoted the development of NSCLC. Our study demonstrated that NUP155 was expected to be a potential target for the treatment of NSCLC.